The Relationship between Service Quality and Customer Satisfaction with the Intention to Choose a Hospital Again - Wulansari, Oktufiani Dwi; Suryanto; Santi, Dyan Evita (Future Science / FSH-PH Publications, 2024)
The aim of this research is to examine the relationship between service quality and consumer satisfaction with the intention to choose a hospital again. The hypothesis in this research is that there is a relationship between service quality and consumer satisfaction with the intention to choose a hospital again. The subjects of this research were 104 respondents who had used hospital services. Data was obtained using the intention to choose hospital return scale, service quality scale and patient satisfaction scale. The results of this study show that there is a positive relationship between service quality and consumer satisfaction with the intention to choose a hospital again (ρ < 0.05). This means that the higher the quality of service and customer satisfaction, the higher their intention to reuse the hospital's services.